Jenis dan Faktor Disrupsi di Kelas, Pencegahan dan Penanganan Guru - Siti Khasinah; Elviana Elviana (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
This study aims to determine the types of disruptive behaviors of students in school classroom and the factors which cause them, as well as teachers’ intervention in preventing and intervening the disruption. All data in this qualitative descriptive study were obtained from interviews with 7 teachers from SMKN 1 Kota Banda Aceh, Lhoksemawe, and Langsa. The results showed that there were various types of disruptions made by students with various factors causing them. It was also found that teachers provided varied interventions in preventing and overcoming disruptive behavior in their classes. Interventions are given according to the disruption that occurs such as extinction, verbal reprimand, punishment, and referrals to outside resources such as other teachers, homeroom teachers, parents, school principals and counseling teachers.